The Relationship Between Socialization Ability And Language Abilities In Preschool Children (3-4 Years) At Playgroup Roudhotul Hikmah Jombang District - Sholeh, M.; Fatma, Inge Devita; Rahayu, Yustina (Universitas Pahlawan Tuanku Tambusai, 2023)
Social skills are the achievement of maturity in social relationships. Socialization skills in children often occur together with language skills in children. Socialization skills in children must also always be honed so that there is no delay in language. The purpose of this study was to determine the relationship between socialization skills and language skills in preschool children (3-4 years) at Playgroup Roudhotul Hikmah Jombang Regency. The design used in this research is Analytic Descriptive. The population is students at Playgroup Roudhotul Hikmah with a sample size of 50 children. The variables in this study are the independent variable of socialization ability and the dependent variable of language ability in children. Data were obtained by distributing questionnaire sheets, and processed with the SPSS computer program. The result of data analysis by using Chi-Square test, obtained calculated probability value 0.095 > 0.05 so that H1 is rejected which means there is no relationship between socialization ability and language ability in preschool children (3-4 years) in Playgroup Roudhotul Hikmah Cukir Jombang. Based on the results of data analysis, socialization skills and language skills in preschool children mostly have normal abilities. Factors that influence the development of socialization are family, maturity, socioeconomic status, and education. And the factors that influence language are biological, cognitive, and environmental.